Electrorefining of Copper at Inclined Electrodes - M. Soliman, Said; M. Ahmed, Abdel-Monem (Asian Journal of Chemistry, 2014)
The rate of electrowinning of copper from acidified CuSO4 was studied under natural convection condition. The factors studied were CuSO4 concentration, the height of cathode, the angle of rotation. It is found that the rate of electrowinning increases by increase concentration of CuSO4, increase of angle of rotation and increase electrode height.